Effects of "El Niño 1997-98" phenomenon on main pelagic resources in Peruvian coast - Ñiquen, Miguel (1999)
Five evaluation cruises for pelagic resources were performed between April1997 and September 1998 on Peruvian coast, these allowed to observe changes in composition by species, distribution, size structure, reproduction, and population levels. These changes are similar to those observed in both El Niño 1972-73 and 1982-83, especially with respect to anchovy biomass decrease and increase of other pelagic species. Considerable changes in anchovy size structure in post-Niño period were observed, while sardine, samasa and Pacific mackerel showed good recruitment. Also the reproductive activity was increased, even in juveniles, with outstanding proliferation of sexual mature sardine with 18-20 cm length, this situation has not been recorded before.